The Promise of Democracy - Žukauskaitė, Audronė (Problemos, 2006)
The article analyses recent critical reflections about the nature of democracy. The first chapter is devoted to the notion of “radical democracy”, as described by Ernesto Laclau and Chantal Mouffe. “Radical democracy” seeks to legitimize conflicts and disagreements because the very moment of the resolution of conflicts denies the antagonistic nature of democracy. The notion of “radical democracy” comes very close to the position of deconstruction, discussed in the second chapter. Jacques Derrida speaks about the “democracy to come”, which means that the fulfillment of democracy is never possible in the present moment. These deconstructivist notions of democracy are contrasted with Slavoj Þiþek’s idea of “real political action”, discussed in the third chapter. Þiþek insists that “real political action” resolves the aporias of decision and changes the very coordinates of democratic imaginary.